In the shadow of sectarianism : law, Shi'ism, and the making of modern Lebanon. - Weiss, Max (Harvard University Press, 2010)
Contrary to the conventional wisdom that sectarianism is intrinsically linked to violence, bloodshed, or social disharmony, Max Weiss uncovers the complex roots of Shi`i sectarianism in twentieth-century Lebanon.